Pediatric acute myeloid leukemia with t(8;21) variant: what is the value on clinical outcome? - Abreu, Juliana C.; Fontes, Raissa M.; Matos, Jesamar C.; Jorge, Fátima G.; Lima, Diego S. (International Journal of Contemporary Pediatrics, 2017)
Acute myeloid leukemia (AML) is characterized by clonal expansion of undifferentiated myeloid precursors that results in the bone marrow (BM) failure. Some cytogenetic alterations can be used to predict the prognosis of the disease. AML with t(8;21), presenting RUNX1/RUNX1T1 gene fusion, is associated to favorable prognosis and it is one of most prevalent structural abnormalities in pediatric AML. Variants of t(8;21) has been described, though the prognostic value of these changes remains controversial, especially in pediatric patients. Thereby, we report a pediatric patient with AML with RUNX1/RUNX1T1 fusion presenting the variant t(1;21;8). The diagnosis was confirmed by myelogram, immunophenotyping, cytogenetics and molecular biology. After the diagnosis, the patient was subjected to chemotherapy and submitted to related allogeneic BM transplant. Until this date, the patient has no clinical complaints, predicting a favorable outcome. The register of variants and its proper follow up contributes to a better understanding of the mechanisms involved in these rearrangements and provides information that may be relevant for an appropriate classification and risk stratification of these patients.